Investigating the neural correlates of urge and the modulatory effects of median nerve stimulation in the context of Tourette syndrome - Houlgreave, Mairi Susan (2023)
Tourette syndrome (TS) is a neurodevelopmental, hyperkinetic disorder characterised by the enduring presence of both motor and phonic tics. Premonitory urge (PU) is thought to be a negative reinforcer of tic expression in TS. Tic expression during fMRI scanning is required as an overt marker of increased urge-to-tic, however this can lead to a loss of large amounts of data due to head movement.